2010
DOI: 10.5694/j.1326-5377.2010.tb03839.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for osteoporosis in Australian residential aged care facilities: consensus recommendations for fracture prevention

Abstract: Older people living in residential aged care facilities (RACFs) are at considerably higher risk of suffering fractures than older people living in the community. When admitted to RACFs, patients should be assessed for fracture risk to ensure early implementation of effective fracture prevention measures. Routine or regular determination of calcium and phosphate serum levels in institutionalised older people is not indicated. Opinion is divided about the value of routine measurements of serum concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 56 publications
(63 reference statements)
0
19
0
1
Order By: Relevance
“…These data are based on patients’ self-reporting and thus it is difficult to draw any firm conclusions. However, the finding could strengthen the impression that the recommended supplement dose of vitamin D in Norway (400 IE vitamin D 3 ) is not enough to maintain an adequate level of vitamin D in elderly individuals, and several authors have recommended 800–1000 IE vitamin D 3 as a daily supplement for the elderly [6,55,56]. …”
Section: Discussionmentioning
confidence: 99%
“…These data are based on patients’ self-reporting and thus it is difficult to draw any firm conclusions. However, the finding could strengthen the impression that the recommended supplement dose of vitamin D in Norway (400 IE vitamin D 3 ) is not enough to maintain an adequate level of vitamin D in elderly individuals, and several authors have recommended 800–1000 IE vitamin D 3 as a daily supplement for the elderly [6,55,56]. …”
Section: Discussionmentioning
confidence: 99%
“…A scoping review of strategies for the prevention of hip fractures in elderly nursing home residents documented that vitamin D supplementation and, in some cases, alendronate and hip protectors were associated with reduced fracture risk [26]. Consensus recommendations for fracture prevention in LTC have been published [27,28]; however, most recommendations are based on data obtained in clinical trials that excluded LTC residents, which may reduce physicians’ confidence in applying them [29]. Recently Rondondi et al demonstrated that in an older population of LTC residents the 10-year fracture probability appeared to be mainly determined by age and clinical risk factors obtained by medical history, rather than by BMD or the presence of vertebral fractures on radiography [30], thereby supporting the concept that prediction rules in LTC may not necessitate evaluation of BMD or imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates (BPs) are drugs prescribed for the treatment and prevention of osteoporosis as well as skeletal metastases in patients suffering from malignant diseases because these drugs act as strong inhibitors of osteoclast‐mediated bone resorption (Duque et al., ; Mahtani & Jahanzeb, ). The two most potent and widely used nitrogen‐containing BPs are zoledronate or zoledronic acid (ZA) and alendronate (ALN).…”
Section: Introductionmentioning
confidence: 99%